Implications Related To Regulation On Corporate Social Responsibility In Indonesia (Study on Law No. 40 of 2007 on Limited Liability Company and Law No. 25 of 2007 on capital investment) - Ageng Bambang Saputro; Iwan Permadi; Supriyadi Supriyadi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Good corporate governance has 5 main principles: openness, accountability, accountability, independence, and equality. Although Law Number 40 of 2007 concerning Limited Liability Companies does not explicitly regulate it, the values of the principle are contained in it. One important principle is accountability, which includes corporate social responsibility (CSR). CSR is the company's commitment to contribute to sustainable economic development by paying attention to economic, social, and environmental aspects. Law No. 40 of 2007 and Law No. 25 of 2007 require the implementation of CSR for companies, but there are vagueness and differences in the definition and scope regulated. This raises problems related to discrimination and potential violations of private property rights of companies. In general, CSR arrangements in Indonesia are still not detailed and clear, especially related to intersections with regional interests and social responsibility to the community. Clarity of arrangements is needed so that CSR can be implemented properly and provide benefits to companies, local governments, and surrounding communities. The problem in this study is the implications caused related to the Regulation on Corporate Social Responsibility in Indonesia and how the form of social responsibility and the form of Corporate responsibility in Indonesia related to the Regulation on Corporate Social Responsibility in Indonesia. This type of research is Normative legal research. The method of approach uses legislative and conceptual approaches. Data sources come from primary and secondary legal subers. The results of this study show that the implications arising related to the regulation on Corporate Social Responsibility in Indonesia, in the UUPT regulation on Corporate Social Responsibility are unclear and overlap with other related laws and regulations. Not all companies related to natural resources carry out social and environmental responsibility, because there is still a perception that the allocation of Corporate Social Responsibility is not mandatory, and in its implementation there is no good control from the government, and there are no firm sanctions for companies that do not channel Corporate Social Responsibility. The form of social responsibility and the form of Corporate responsibility in Indonesia related to the Regulation on Corporate Social Responsibility in Indonesia can vary, depending on the needs and priorities of the company and the surrounding community. Corporate Accountability that implements CSR is needed to hold stakeholders accountable. The form of accountability can be: CSR report: a report that explains the CSR activities that have been carried out by the company, the impact that has been achieved, and the obstacles faced. CSR audit: an independent audit to ensure that CSR activities have been carried out in accordance with established standards and policies. Dialogue with stakeholders: open dialogue with stakeholders to obtain input and suggestions related to CSR implementation.